A single session of straight line and change-of-direction sprinting per week does not lead to different fitness improvements in elite young soccer players - Beato, M.; Bianchi, M.; Coratella, G.; Merlini, M.; Drust, B. (The Journal of Strength and Conditioning Research, 2022)
Effective prescription is especially important in elite soccer players, who have a very limited time to dedicate to specific physical development as a consequence of factors such as congested match schedules and travel. The aim of this study was to compare the effectiveness of one repeated-sprint training (RST) session per week over an 8-week period on physical performance. A second aim was to compare the effect of RST involving straight sprints (RST-SS) or changes of direction (RST-COD). This study used a randomized pre-post parallel group trial design. The elite soccer players were randomly assigned to either an RST-SS (10 players) or RST-COD (10 players). RST-SS was 3 sets of 7 × 30-m sprints with 20-second and 4-minute recovery between sprints and sets, respectively. RST-COD was 3 sets of 7 × 20 + 20 m (one COD of 180°) shuttle sprints with 20-second and 4-minute recovery between sprints and sets, respectively. The physical tests selected were long jump, repeated-sprint ability (RSA) best, RSA mean, 505 agility test, Yo-Yo recovery level 1, 10, 30, and 40 m sprints. RST-SS reported unclear variations in long jump, sprint 30 m, sprint 40 m, RSA best, and RSA mean, whereas RST-COD showed unclear and trivial variations in sprint 10 m, sprint 30 m, sprint 40 m, RSA best, and RSA mean. The between-group analysis did not report any statistical difference. In conclusion, a single session of RST-SS and RST-COD do not improve soccer-specific fitness indicators in elite youth players during the season.